2017
DOI: 10.4317/jced.54271
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the relationship between dental caries number and salivary level of IgA in adults

Abstract: BackgroundDental caries are the most common mouth infectious disease and also chronic disease of childhood. Saliva plays different roles in oral cavity; for example, salivary immunoglobulins play significant role in body and oral immunity. Various studies were conducted on the different effects of IgA on oral cavity, especially dental caries, and reported controversial results. The current study aimed to compare salivary IgA level at different stages of dental caries in adults.Material and MethodsA total of 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…The overall results of the correlation between salivary s-IgA levels and caries were shown in Figure 3 . Salivary s-IgA levels in caries patients (mean ± SD) ranged from 2211.00 ± 778.68 [ 45 ] to 0.1472 ± 0.0710 μg/ml [ 21 ], while those in healthy controls ranged from 3155.10 ± 489.30 [ 5 ] to 0.0939 ± 0.0239 μg/ml [ 21 ]. Due to the heterogeneity of I 2 >50% in the study, the random effect model ( P <0.001) was adopted for data consolidation analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The overall results of the correlation between salivary s-IgA levels and caries were shown in Figure 3 . Salivary s-IgA levels in caries patients (mean ± SD) ranged from 2211.00 ± 778.68 [ 45 ] to 0.1472 ± 0.0710 μg/ml [ 21 ], while those in healthy controls ranged from 3155.10 ± 489.30 [ 5 ] to 0.0939 ± 0.0239 μg/ml [ 21 ]. Due to the heterogeneity of I 2 >50% in the study, the random effect model ( P <0.001) was adopted for data consolidation analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Salivary IgA secretions are believed to be factors that protect dental caries by controlling the growth of cariogenic oral microflora, preventing pathogenic adhesion, and activation of enzymes and toxins from bacteria [26]. Increased levels of sIgA in caries patients are an immune system response as a protective mechanism against the process of dental caries and S. mutans are active in the oral cavity [18]. Neutrophils in saliva are the first defense cells against pathogenic microbes.…”
Section: Discussionmentioning
confidence: 99%
“…There are three subclasses of immunoglobulins found in saliva, namely, IgA, IgG, and IgM. IgA is the most common immunoglobulin in saliva (about 60%) [18]. The salivary secretory immunoglobulin A (sIgA) can bind specifically to the epitope of S. mutans section, so bacteria cannot bind to the salivary pellicle and S. mutans will not colonize the salivary tooth surface [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Atler (2007) show that bacteriostatic, bacteriolytic and bactericide characteristics of lysozyme are based on its ability to destroy peptidoglycans of the cell wall and finally lead to their lyses. The researches of (Chawda et al 2011;Chereda et al 2012;Haeri-Araghi et al 2018) demonstrated very controversial findings about the content and the role of s-IgA in oral liquid of children resistant and sensitive to dental caries.…”
Section: Introductionmentioning
confidence: 99%